Analisis Kedudukan Surat Keterangan Hak Milik dalam Sengketa Agraria (Studi Putusan Pengadilan Tata Usaha Negara Manado Nomor : 25/G/2023/PTUN. MDO) - Hamdani, Aristiono; Huda, Miftahul (Jurnal HUKUM BISNIS, 2025)
Government Regulation Number 18 of 2021 Article 97 concerning Management Rights, Land Rights, Apartment Units and Land Registration states that "Certificate of Ownership Rights, Compensation Certificate, Village Certificate and others of the same type which are intended as Certificate of Ownership Rights for land can only be used as a guide for land registration. However, on the other hand, if the certificate of ownership rights can only be used as a guide for land registration, various new problems will arise, therefore the author is interested in discussing the position of the certificate of ownership rights in the Manado State Administrative Court Decision Number: 25/G/2023/PTUN. MDO with the aim of knowing the Position of the Certificate of Ownership Rights as Proof of Ownership of Land Rights and Knowing and Analyzing the Position of the Certificate of Ownership Rights in the Manado State Administrative Court Decision Number: 25/G/2023/PTUN. MDO will then be examined by the author using a normative research method with a legal analysis approach or also called legal analysis, namely research conducted by analyzing applicable legal rules (Legal Research) so as to produce conclusions so as to produce conclusions In terms of the position of the evidence of the Dorneka Tawatua Land Ownership Certificate, it is valid and recognized as evidence, but proof of ownership of land rights based on the Land Ownership Certificate alone is not enough, but must also be proven by physical data and other legal data. However, Decision Number: 25 / G / 2023 / PTUN. MDO The Plaintiffs' Lawsuit was not accepted because the Dorneka Tawatua Land borders the land. The disputed object certificate is not included in the disputed object certificate so that there is no clauseal relationship with the disputed object certificate. Keywords: Land Ownership Certificate, Agrarian Dispute, Jurisprudence